METABOLIC PROFILE AND VASCULAR STIFFENING: RELATIONSHIPS IN MIDDLE-AGE NORMOTENSIVE PATIENTS. (June 2018) - Gonzalez, S.A.; Svane, J. Chiabaut; Kempny, P.; Schiavone, M.; Castellaro, C.
Abstract : Objective: a-To determine univariate associations between lipid metabolism markers (LMM) and glucose metabolism markers (GMM) with pulse wave velocity (PWV) in normotensive subjects (NT) and b-To evaluate independent relationships between LMM, GMM with PWV in NT. Design and method: 380 subjects were evaluated consecutively during a primary prevention programme, that includes blood sample and arterial stiffness evaluation. After applying exclusion criteria (age below 18/above 80 years, hypertension, previous diagnostic of diabetes, glucose > 126 mg/dl and/or HbA1c > 6.4%, cardiovascular event) 165 NT were included (49.8 ± 10.7 years, 120 ± 12/79 ± 10 mm Hg, 57% male sex). BP was measured (ESH) prior to PWV determinations (Mobil-O-Graph PWA monitor, I.E.M. GmbH, Germany). Low-density cholesterol (LDLc), high-density cholesterol (HDLc), triglycerides (TG), glucose (GLU), HbA1c and insulin (INS) were determined, and HOMA index and body mass index (BMI) were calculated. LMM and GMM markers were tested according to quintiles of PWV (ANOVA). Elevated PWV (ePWV) was defined as > percentile 90% by age (Arterial Stiffness' Collaboration database). Age, sex, BMI, systolic BP, and metabolic markers -those were significantly different in univariated analysis- were tested in a logistic regression, with ePWV as dependent variable. Results: LMM (HDLc, LDLc and TG) showed no associations through quintiles of PWV (p > 0.05 in all cases). GLU and HbA1c showed significant increments across quintiles of PWV (p < 0.001 and p = 0.01, respectively), while INS and HOMA did not (p = 0.24 and p = 0.12, respectively). Of the entire NT population, 16% presented ePWV. In logistic regression, age, systolic BP and HbA1c were independent predictors of ePWV (fig). Figure. No caption available. Conclusions: HbA1c, a marker of glucose metabolism, was a predictor of early vascular stiffening in this cohort of middle-age normotensive patients, beyond other established factors, as age and blood pressure. This finding could be showing an early enzymatic glycation of arterial wall proteins in normotensives, with AGE's formation and progressive stiffening of conductance arteries.